Culturally Situated Do-It-Yourself Instructions for Making Protective Masks: Teaching the Genre of Instructional Design in the Age of COVID-19. (January 2021) - Oswal, Sushil K.; Palmer, Zsuzsanna B.
This article employs cross-cultural communication approaches to teaching instructional design in the times of COVID-19 pandemic. Focusing on instructions from France, India, Spain, and the United States for making protective masks, the authors highlight how the writers and designers of these four documents from each culture approach their audiences, organize their DIY instructions, make language choices, employ images and other illustration devices, and culturally persuade users. While acknowledging cultural differences, the authors urge students to identify and adopt design strengths from diverse cultures in their own ideas about composing instructions.